(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Oxidative stress has been established among the key causes of both metabolic and cellular dysfunctions, thus developing an efficient natural antioxidant is highly required. This work profile the bioactive and examines the antioxidant capacity of the hypocotyl fractions of Borassus aethiopum (the palm tree) through in vitro and in-vivo assays. The phytochemical tests revealed a high content of total phenolic (875 ± 34.5 mg/g) than flavonoids (15.2 ± 0.57 mg/g) in the hypocotyl of B. aethiopum. A variable antioxidant activity was established by the various solvent fractions, with aqueous fraction having the highest activity in vitro as demonstrated its lowest IC50 value against DPPH radical scavenging activity (23.8 ± 0.5 µg/mL) and total antioxidant power (10.6 ± 0.2 µg/mL). Similarly, FTIR spectra revealed dominant O–H, C–H, C=O, and C–N functional groups characteristic of phenols, carboxylic acids, alkanes, and amines, confirming the presence of redox active chemical classes. GC–MS analysis identified several antioxidant associated metabolites, including thymol acetate, tyrosol, 3 nitrochalcone, retinal, α ionone derivatives, 3 aminosalicylic acid, hydroquinone derivatives, diosgenin, and lupeol. The in vivo assessment in diabetic rat model demonstrated biochemical modulation consistent with antioxidant activity. Extract treated groups showed reduced malondialdehyde levels (e.g., 0.54 ± 0.06 nmol/mg at 250 mg/kg) relative to diabetic controls (0.87 ± 0.16 nmol/mg), alongside increases in superoxide dismutase (0.55 ± 0.04 U/mL at 500 mg/kg) and dose dependent alterations in catalase activity. Together, these findings demonstrate that B. aethiopum hypocotyl possesses a robust antioxidant signature driven by phenolic abundance, redox active metabolites, and modulation of endogenous antioxidant enzymes, supporting its potential as a natural source of antioxidant compounds.